Juridical Implications for Notaries Who Commit Malpractice in Making Authentic Deeds in Kendal Regency - Ardiansah, M. Irwan (Jurnal Konstatering, 2024)
Notaries who are authorized officials who have the authority to make authentic deeds can be prosecuted for acts of malpractice in making deeds. Claims against notaries who commit negligence or acts of malpractice can be reported and submitted to the Notary Honorary Council (MKN) and also the police. This research aims to find out and also analyze the consequences and also the notary's responsibility for the malpractice he or she commits. This research will also analyze the legal protection that the notary gets if they are suspected of committing malpractice in the process of making an authentic deed. The research approach used in this thesis is a sociological juridical legal research method. This research specification uses descriptive analysis. The types of data used in this research are primary data, secondary data and tertiary data as well as secondary data containing books and other supporting documents. Collecting research data using interview techniques or library materials. The consequences that occur when malpractice in making deeds occur are that the notary will receive legal repercussions at trial in the form of paying the compensation demanded. Apart from that, a notary who commits malpractice can also have his position as a notary revoked honorably, dishonorably, or temporarily by the Ministry of Law and Human Rights. Socially, notaries no longer have the trust of the public.